Os ditos e os não ditos sobre as mulheres nos livros didáticos: representações de gênero na coleção didática “História – das cavernas ao terceiro milênio” - Cunha, Ana Cláudia Lima de Oliveira (2022)
This work aims to analyze the way in which the history of women from the perspective of gender relations was incorporated as historical knowledge in the didactic collection History: from caves to the third millennium, destined to the modality of Basic Education. The methodological strategy employed was descriptive and analytical in nature. In a first stage, a literature review was made about the incorporation of women and the gender category in historiography, as well as the literature about the textbook, especially history. Next, we analyzed the textbooks of the mentioned collection, seeking to understand how the participation of women in the different historical processes was presented and the way gender relations were approached. It was found, through these analyses, that the didactic narrative employed in the collection studied places women mostly on the margins of the historical events presented, and their images are sometimes decontextualized and their experiences highlighted separately to the main text. Gender relations have rarely been identified and questioned. Finally, a website was created in order to disseminate information about gender issues and provide reflection on the need for their incorporation in history classes.